Monetary and Fiscal Policies and the Dynamics of the Yield Curve in Morocco - Ahokpossi, Calixte (IMF Working Papers; Working Paper ;, 2016)
We estimate the latent factors that underlie the dynamics of the sovereign bond yield curve in Morocco during 2004-14 based on the Dynamic Nelson-Siegel model. On this basis, we explore the interaction between macroeconomic variables and the yield curve, which is of direct relevance to macroeconomic policy-making. In Morocco's context, we find that tighter monetary policy increases short-end maturities, and that the impact is small and short-lived. Economic activity is also briefly but significantly impacted, suggesting that even under a pegged exchange rate, monetary policy autonomy and effectiveness can be increased through greater central bank independence. Fiscal improvements significantly lower yield levels. Policy conclusions are that improvement in the fiscal and monetary policy frameworks, as well as greater financial sector development and inclusion, could benefit Morocco and strengthen the transmission mechanisms and effectiveness of macroeconomic policies.